LEGAL OVERVIEW OF COMPENSATION FOR LAND IN THE DEVELOPMENT OF PT. PLN'S SUTET TOWER NETWORK IN THE TAKTAKAN DISTRICT OF SERANG CITY, BANTEN PROVINCE - Ahmad Jakaria Ansori (Transpublika Publisher, 2024)
The implementation of land compensation to the community for the construction of the Extra High Voltage Transmission Network (SUTET) by PLN falls under the Ministry of Energy and Mineral Resources (ESDM). The Ministry of Energy and Mineral Resources released Ministerial Regulation (Permen) ESDM number 13 of 2021 regarding Free Space and Minimum Clearance Distance for Electric Power Transmission Network and Compensation for Land, Buildings, and/or Plants Located in the Free Space of Electric Power Transmission Network. This regulation was enacted by Minister of ESDM Arifin Tasrif on June 17, 2021, and took effect upon its promulgation on June 17, 2021. With this regulation, the rights of the community whose land is traversed by the transmission will receive compensation. However, the regulation does not comprehensively address the impact of the development and compensation for the transmission lines of 500 kV or 150 kV, leading to injustice and legal uncertainty. PLN's responsibility for the land value of the community affected by the construction of the SUTET transmission network is limited. In providing compensation to the community whose land is traversed by the Extra High Voltage Transmission Line (SUTET), PT PLN follows existing regulations. PLN refers to Ministerial Regulation No. 01.P/47/MPE/1992 on SUTET Free Space and SUTET for Electricity Distribution Article 5 paragraph (3) concerning land for establishing support structures, including buildings and plants on that land, which must be cleared and compensated.